Propuesta estratégica de Marketing Digital para incrementar la captación de alumnos del Instituto de Educación Superior Tecnológico Público Manuel Gonzales Prada del Distrito El Porvenir - Provincia de Trujillo 2019-I - Alvarado Ramos, Jorge Luis (2018)
ABSTRACT This study aims to present the strategic Digital Marketing proposal to increase the recruitment of students of the Institute of Higher Education Technological Public "Manuel Gonzales Prada" District El Porvenir, referred to the question "Digital Marketing as a strategy of Marketing Communication Will increase the recruitment of students to the Institute of Higher Education Technological Public "Manuel Gonzales Prada" - El Porvenir District, Province of Trujillo ?; Whose hypothesis is: Digital Marketing as a strategy of Marketing Communication will significantly increase the recruitment of students to the Institute of Higher Education Technological Public "Manuel Gonzales Prada" - El Porvenir District, Province of Trujillo; And, dependent variable: Student enrollment at the "Manuel Gonzales Prada" Technological Higher Education Institute - El Porvenir District, Province of Trujillo. With the proposal to attract more students, the following objective was established: To elaborate a Digital Marketing strategy proposal to increase the number of Postulants to the Institute of Higher Education Technological Public "Manuel Gonzales Prada". We used the descriptive design as well as the following methods: Deductive-inductive, analytical-synthetic and statistical. The study population consisted of 18,301 young people, from which a representative sample of 100 respondents was established. Application as survey data collection technique. In this work, it is demonstrated that the digital marketing application proposal to the Manuel Gonzales Prada Institute, will increase the number of applicants, through the different online marketing tools such as: online advertising, both on their website and on social networks. It is also appreciated that the digital marketing budget is much lower compared to traditional or offline marketing.